1998
DOI: 10.1023/a:1008349427337
|View full text |Cite
|
Sign up to set email alerts
|

High-dose therapy with autologous haematopoietic support in patients with transformed follicular lymphoma: A study of 27 patients from a single centre

Abstract: It is appropriate to consider HDT for younger patients with FL-t in remission. Repeat biopsy should be considered for patients with recurrent disease. There is a risk of late MDS in patients undergoing this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 23 publications
2
42
1
Order By: Relevance
“…17,18 Several later studies with limited numbers of patients have not shown a difference in outcomes, potentially secondary to inadequate power. 11,12,16,19,20 Only one study of 50 patients with transformed disease demonstrated no difference in outcomes indirectly, comparing the patients to historical controls with de novo follicular or de novo large cell lymphoma. 21 In our cohort of 49 patients, among whom 22 had transformed disease, histologic transformation was not a statistically significant predictor of OS or EFS by multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Several later studies with limited numbers of patients have not shown a difference in outcomes, potentially secondary to inadequate power. 11,12,16,19,20 Only one study of 50 patients with transformed disease demonstrated no difference in outcomes indirectly, comparing the patients to historical controls with de novo follicular or de novo large cell lymphoma. 21 In our cohort of 49 patients, among whom 22 had transformed disease, histologic transformation was not a statistically significant predictor of OS or EFS by multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies investigating intensive chemotherapy regimens with autologous stem cell support in an effort to improve response and survival [36][37][38][39][40][41][42][43][44] (Table 4). In 1989, Schouten et al 38 reported 10 patients who had undergone autologous transplantation for HT at the University of Nebraska.…”
Section: Autologous Transplantationmentioning
confidence: 99%
“…In addition to TRM, outcomes from autologous transplantation are adversely affected by a 2-15% incidence of second malignancies, predominantly MDS and AML. 9,[38][39][40][41] Though the small absolute numbers precluded analysis, several investigators proposed the cause to be the cumulative risk of alkylating agents and TBI. With the 3 cases of MDS in Berglund's series occurring at 4, 5, and 7 years post-transplant, the concern for increasing incidence of MDS/AML with longer follow-up time arises.…”
Section: Autologous Transplantationmentioning
confidence: 99%
“…[4][5][6][7][8] This event typically carries a poor prognosis, 2,7 although durable remissions have been observed in a subset of individuals following high-dose therapy. 9,10 Transformation provides an important model for the study of oncogenesis and a number of recurring secondary events are recognised that may be of mechanistic significance. These include acquisition of recurrent chromosomal aberrations including loss of 17p and gains at 12q, [11][12][13][14] inactivation of CDKN2A and CDKN2B, 15 dysregulation of c-MYC 16,17 and translocations, 18 gains 13 and mutations involving BCL-6.…”
Section: Introductionmentioning
confidence: 99%